UPAYA PENANGGULANGAN SISA MATERIAL PASCA BENCANA BANJIR BANDANG DI NAGARI ANDALEH BARUH BUKIK KECAMATAN SUNGAYANG - Davison, Emil; Sabila, Belia; Juita, Erna; Zuriyani, Elvi (Jurnal Spasial, 2024)
Flash Flood or "Galodo" disaster hit West Sumatra around Mount Merapi on Saturday, May 11, 2024. Several areas such as Nagari Andaleh, Pandai Sikek, Limo Kaum, and several areas in Agam and other Tanah Datar were hit by this flood. Galodo is a river flow that flows downstream with sediment such as sand and gravel. Flash floods or galodo occur because the static balance between the shear force generated by the flow is greater than the shear force of the sediment mass that holds it. Flash floods or galodo occur because of holding Flash floods or galodo occur because. Areas included in the danger category are areas around Mount Merapi within a radius of 5 km from the center of activity. To avoid the danger of lava flows, especially in areas with low topography and deep valleys along the river flow that originates from around the peak crater, and pay attention to the currently active crater on the western peak which has a greater threat of eruption in Nagari Baruh Bukik, Sungayang District, Tanah Datar Regency, West Sumatra Province. Contributing factors include slope gradient, elevation class, soil texture, rainfall, land use, and buffers from the river network.